1995
DOI: 10.1177/106002809502901213
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione in Health and Disease: Pharmacotherapeutic Issues

Abstract: The list of potential indications for modulation of GSH is extensive and broad. This review introduces clinicians to what GSH is, its basic chemistry, and some areas of active research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(128 citation statements)
references
References 72 publications
0
125
0
3
Order By: Relevance
“…Other studies have shown that PDT, via NF-kB, induced the up-regulation of γ-glutamylcysteine synthetase expression in response to oxidative stress-induced GSH depletion (30). Furthermore, discrepancies have been noted concerning the relationship that exists between antioxidant levels and tumor damage, as GSH levels have been reported to be increased, decreased or unaltered following PDT (31). Additionally, it has been shown that the activation of apoptosis-executing caspases actually requires sustained glutathione levels as these proteases possess an essential cysteine thiol in the active site (29).…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have shown that PDT, via NF-kB, induced the up-regulation of γ-glutamylcysteine synthetase expression in response to oxidative stress-induced GSH depletion (30). Furthermore, discrepancies have been noted concerning the relationship that exists between antioxidant levels and tumor damage, as GSH levels have been reported to be increased, decreased or unaltered following PDT (31). Additionally, it has been shown that the activation of apoptosis-executing caspases actually requires sustained glutathione levels as these proteases possess an essential cysteine thiol in the active site (29).…”
Section: Discussionmentioning
confidence: 94%
“…In fact, erythropoietin might have been responsible for aggravating the photosensitivity in our patient. Glutathione deficiency resulting from sun exposure and oxidative stress might also be responsible for the development of pseudoporphyria (6). N-acetyl cysteine increases the intracellular glutathione biosynthesis in this setting (7), and its long-term use is beneficial in the treatment of pseudoporphyria.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase, reductase, transferase(s) and glutaredoxin all utilize GSH in reactions that remove peroxide, as well as potential endogenous and exogenous toxins, control the redox state of the cell and regulate protein function through thiolation and dethiolation. This network of enzymes using GSH as substrate have been implicated in DNA synthesis and repair, protein synthesis, amino acid transport, and enzyme activation or inactivation (Lomaestro & Malone 1995). GSH may also act as a redox modifier of some ionotropic currents (Ogita et al 1995).…”
Section: Abstract Oxidative Stress; Glutathione Ethyl Ester; Neurodegmentioning
confidence: 99%